Making a “Bangladeshi diaspora”: Migration, group formation and emplacement between Portugal and Bangladesh - Mapril, José (Migration Letters, 2021)
In 1996, Appadurai argued that imagination is an essential element in the creation of cross-border political forms. Electronic media, for example, establishes links across national boundaries, linking those who move and those who stay. In his argument, these diasporic public spheres were examples of post-national political worlds and revealed the erosion of the nation-state in the face of globalisation and modernity. In this paper, I draw inspiration on this concept of diasporic public sphere but to show how these imaginaries are intimately tied to forms of group making and emplacement in several contexts. This argument is based on an ethnographic research about the creation of a transnational federation of Bangladeshi associations – the All European Bangladeshi Association (AEBA) – in the past decade, its main objectives and activities. Through the analysis of an AEBA event that took place in Lisbon, I want to show the productive dialectic between diasporic imaginaries, group formation and emplacement processes between Portugal and Bangladesh.